2016
DOI: 10.6061/clinics/2016(12)03
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of NANOS3 in Brazilian women with primary ovarian failure

Abstract: OBJECTIVES:Primary ovarian failure is a rare disorder, and approximately 90% of cases are of unknown etiology. The aim of this study was to search for mutations in NANOS3, a gene that was recently related to the etiology of primary ovarian failure, in a group of Brazilian women.METHODS:We screened for NANOS3 DNA variants in 30 consecutive women who were previously diagnosed with primary ovarian failure, of unknown etiology and compared the results with those from 185 women with normal fertility. The NANOS3 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although the structure of P100 is solved (Rother et al 1992), the molecular biology of PATL2 variants is otherwise unexplored. However, infertility-linked variants in another translational regulator, NANOS3, suggest that translational regulation may be a key pathogenic mechanism in infertility (Wu et al 2013, Santos et al 2014, Sousa et al 2016.…”
Section: R23mentioning
confidence: 99%
“…Although the structure of P100 is solved (Rother et al 1992), the molecular biology of PATL2 variants is otherwise unexplored. However, infertility-linked variants in another translational regulator, NANOS3, suggest that translational regulation may be a key pathogenic mechanism in infertility (Wu et al 2013, Santos et al 2014, Sousa et al 2016.…”
Section: R23mentioning
confidence: 99%
“…NANOS3 gene mutations were found in a group of infertile men, but no causation was detected [11]. On the other hand, two out of four NANOS3 mutations were detected to be linked to premature ovarian insufficiency (POI) in infertile women [13][14][15][16]. Moreover, Santos et al demonstrated that one NANOS3 mutation linked to POI causes increased apoptosis of cultured cells, suggesting an anti-apoptotic role of human NANOS3 [14], as was shown for a mouse orthologue.…”
Section: Introductionmentioning
confidence: 95%